EFFECT OF SEASONS ON THE PERFORMANCE OF DIFFERENT VARIETIES OF CHICKS IN MEGHALAYA (Indian Journal of Animal Production and Management, 2015)
Series of experiments were conducted to study the performance of Vanaraja, Gramapriya and Indigenous chicks under deep litter system of rearing from 0-8th weeks of The performance of chicks in Meghalayaage in pre-monsoon, monsoon and post-monsoon seasons. The results revealed better performance of chicks in pre-monsoon compared to monsoon and post monsoon seasons in terms of body weight, growth rate and FCR although chick mortality was found to be significantly lower (p
Keywords: Seasons; erformance; Vanaraja; Gramapriya; Indigenous chicks